2015
DOI: 10.1039/c5cp02765a
|View full text |Cite
|
Sign up to set email alerts
|

Double hysteresis loops and large negative and positive electrocaloric effects in tetragonal ferroelectrics

Abstract: Phase field modelling and thermodynamic analysis are employed to investigate depolarization and compression induced large negative and positive electrocaloric effects (ECEs) in ferroelectric tetragonal crystalline nanoparticles. The results show that double-hysteresis loops of polarization versus electric field dominate at temperatures below the Curie temperature of the ferroelectric material, when the mechanical compression exceeds a critical value. In addition to the mechanism of pseudo-first-order phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…In turn, depending on temperature, field strength, and strain both the conventional and inverse ECE can coexist . The coexistence of conventional and inverse ECE in one material, which has also been found in phase‐field simulations, might thus explain the partly inconsistent reports on the ECE in thin films.…”
Section: Different Examples Of Inverse Ec Responsementioning
confidence: 99%
“…In turn, depending on temperature, field strength, and strain both the conventional and inverse ECE can coexist . The coexistence of conventional and inverse ECE in one material, which has also been found in phase‐field simulations, might thus explain the partly inconsistent reports on the ECE in thin films.…”
Section: Different Examples Of Inverse Ec Responsementioning
confidence: 99%
“…While typical hysteresis effects are positive, recent work has shown that negative hysteresis is far more common than may be expected. Examples of negative hysteresis in laser physics (e.g., [ 65 69 ]), and material science (e.g., [ 70 72 ]) abound. But negative hysteresis has also received increasing attention in perception, in particular in the field of ecological psychology (see e.g., [ 56 , 57 , 73 – 78 ] and also the discussion of multistability later in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, composites combining relaxor terpolymer P(VDF-TrFE-CFE), Ba 0.67 Sr 0.33 TiO 3 ceramics, and BNNSs show a huge electrocaloric temperature change of over 50 K at room temperature under a ultrahigh electric field of 2500 kV/cm, 134 while relaxor composites based on P(VDF-TrFE-CFE) and PMN-PT 136 are also demonstrated to be comparable to this performance (see Table I). Testifying the giant electrocaloric effect in other nanostructures such as nanoparticles, 106,111,171 nanotubes, 172 and nanowires 173 is highly desired since recent experimental results demonstrated that electrocaloric effect in polymer nanocomposites can be tailored by the morphology of the ferroelectric nanofillers. 169 As a result, the idea of using nanowires for towards wearable cooling applications has been achieved in highly bendable and stretchable Ba 0.67 Sr 0.33 TiO 3 nanowires arrays.…”
Section: Perspectivesmentioning
confidence: 99%